The Effectiveness of The Independent Teaching Platform (PMM) in Increasing The Competency of Primary and Secondary Education Teachers - Soedjono Soedjono (Universitas PGRI Semarang, 2023)
The Ministry of Education and Culture's intervention in supporting the implementation of the independent curriculum, from policy to technical matters, is carried out because the experience of implementing a top-down curriculum experienced many obstacles. Among the five forms of technical intervention carried out by the Ministry of Education and Culture which are in direct contact with teachers, both teachers at driving schools and non-moving schools, are the independent teaching platform or “Platform Merdeka Mengajar” (PMM). The extent to which the effectiveness of the independent teaching platform (PMM) can increase teacher competence in achieving learning in the classroom is the aim of this research. The methods used are the critical method, dialectical method, and scholastic method. This research is included in library research. The author tries to find data, and theories related to the issues raised in various literature or references that the author finds and then compares them using the method mentioned above. The research results show that the content of the independent teaching platform meets the dimensions and indicators that can increase teacher competence. After learning by utilizing PMM, teacher competence increases according to the indicators that have been determined, so PMM has very high effectiveness in increasing teacher competence in their learning performance.